Closing the loop: recycling of MAPbI3 perovskite solar cells - Wu, Zhenni; Sytnyk, Mykhailo; Zhang, Jiyun; Babayeva, Gülüsüm; Kupfer, Christian; Hu, Jin; Arnold, Simon; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Energy and Environmental Science, 2024)
Closed-loop recycling is crucial in the rapidly expanding era of photovoltaic deployment. Yet, the recycling of commercial silicon photovoltaic modules presents challenges due to laborious component separation. In contrast, layers in solution-processed solar cells can be separated with relative ease through selective dissolution. In this study, we report on the recovery of every layer in a planar MAPbI3 perovskite solar cell using a layer-by-layer solvent extraction approach, followed by purification or modification to restore quality. This method potentially allows for up to 99.97% recycled mass, thereby conserving resources and reducing waste. We assessed material quality by substituting each fresh material with its recycled equivalent during solar cell production. Subsequently, solar cells were fabricated with either several or all layers comprising recycled materials. Every combination yielded efficiency comparable to cells constructed exclusively with fresh materials, demonstrating the efficacy of the developed recycling process. Our mass and value analysis highlights ITO glass has the highest recycling priority and the need for circular utilization for by-product chemicals, especially cleaning agents. Techno-economic projections suggest that the proposed recycling procedure has the potential to afford substantial cost savings. In the lab, recycling could reduce material costs by up to 63.7%, in industrial manufacturing by up to 61.4%. A life cycle assessment reveals this recycling method can reduce environmental impacts.
CRIS-Team Scopus Importer:2024-06-07

Cradle to Cradle Recycling of Perovskite Solar Cells - Wu, Zhenni; Babayeva, Gülüsüm; Zhang, Jiyun; Sytnyk, Mykhailo; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
Cradle-to-cradle recycling plays an important role in resolving one of the major upcoming challenges for photovoltaics in the energy transition-resource management. As photovoltaic production continues to grow, it absorbs a vast amount of resources. Cradle-to-cradle recycling is essential to keep these resources available perpetually and minimize waste generation. To achieve this, a new design paradigm for solar panels that puts recycling in its center is needed. In this study, we show first results of a perovskite solar cell that was created using such a design paradigm. We created a device with 18.1% efficiency and an architecture that facilitates disassembly of the functional layers. We show that the absorber material, MaPbI3 was used for the test device, can be recycled without causing a loss of solar cell efficiency.
CRIS-Team Scopus Importer:2024-12-16